Correlação entre o número e tempo de duração das refeições e a presença de sinais gastrointestinas em pacientes com mais de 24 meses de cirurgia bariátrica - GOMES, Bruna Gusmão (2023)
Obesity is a chronic disease of multifactorial origin, which can lead to the appearance of other diseases. In the context of severe obesity, conservative treatments have very little significant results in relation to weight loss, so that surgical intervention has become the main means for treating and controlling severe obesity and restoring health status. However, eventually, the postsurgical course with unwanted gastrointestinal events. Thus, the objective of this study is to identify the correlation between the amount and time of meals associated with the presence of gastrointestinal signs in patients with more than 24 months of bariatric surgery. To this end, a crosssectional, descriptive and analytical study was carried out with women, aged between 18 and 59 years, who underwent bariatric surgery, using the RYGB or Vertical Gastrectomy method as surgical techniques, for at least 24 months in the period in which it was performed. up data collection. A questionnaire was used during the consultations, the data were tabulated using the Microsoft Office Excel 2010 software. For statistical analysis, the Statistical Package for Social Science (SPSS) software, version 24.0 was used. The descriptive results were expressed in measures of central tendency and dispersion, the KolmogorovSmirnov normality test was applied to verify the sample distribution. Bivariate correlations were performed using Spearman's correlation test, where an error of 5% was assigned. The collected data indicate that most of the sample had dumping syndrome as well as food intolerance, as for the gastrointestinal symptoms it was evidenced that the most referred were nausea, vomiting and distended abdomen, there was also an inverse correlation between dysphagia and dyspepsia and meal time and inverse correlation between number of meals and vomiting, in relation to anthropometry, a direct correlation was identified between the number of meals eaten and loss of excess weight, and an inverse correlation between the number of meals eaten and weight regain. Given the relevance of surgical intervention for coping with severe obesity, the importance of investigating the symptoms associated with bariatric surgery, which may affect the patient's quality of life and nutritional status after the surgical procedure, is highlighted.